A NOVEL METHOD FOR QUANTITATIVE DETERMINATION OF ACECLOFENAC IN BULK DRUG AND TABLETS USING SODIUM SALICYLATE AS A HYDROTROPIC SOLUBILIZING AGENT - Shruti Moondra; R. K. Maheshwari (Wolters Kluwer Medknow Publications, 2010)
In titrimetric analysis costlier organic solvents are more often employed tosolubilize the poorly water-soluble drugs. Volatility and pollution are drawbacks of suchsolvents. Various techniques are employed to enhance the aqueous solubility of poorlywater-soluble drugs. Hydrotropic solubilization phenomenon has been widely used toenhance the aqueous solubility of large number of poorly water-soluble drugs. Aqueoussolubility of aceclofenac bulk drug [a poorly water-soluble NSAID] was enhanced to agreat extent i.e., 400 folds with 2.5 M sodium salicylate. The primary objective of thepresent investigation was to employ this hydrotropic solution to extract the drug from itsdosage forms, precluding the use of costlier organic solvents. The proposed method ofanalysis is new, simple, accurate, environmentally friendly and reproducible. Statisticaldata proved the accuracy, reproducibility and the precision of the proposed method. Theresults of titrimetric analysis by use of hydrotropy compared very well with the results ofPharmacopoeial method.